Genome-Wide Characterization of the R2R3-MYB Gene Family in Diospyros oleifera - Kang Ji; Cuiyu Liu; Kaiyun Wu; Zhihui Yue; Yi Dong; Bangchu Gong; Yang Xu (Agriculture, 2023)
The MYB gene family is one of the largest transcription factor families, which is clustered into four subfamilies according to the number of imperfect amino acid sequences repeats in their conserved MYB domain. R2R3-MYB is the largest subfamily that plays a diverse role in plant growth and development as well as adversity stresses. Diospyros has a wide range of applications in biomedical science and the food, wood, and chemical industries. Among these species, Diospyros oleifera can be used as a model plant for the Diospyros genus and the Ebenaceae family. Although the genome sequence of Diospyros oleifera was recently published in our previous work, bioinformatics and expression pattern analysis of the MYB gene family are limited. Here, we present the findings of a genome-wide analysis and the expression profiles of the R2R3-MYB transcription factor in Diospyros oleifera. A total of 129 R2R3-MYB genes were identified and classified into 28 groups (C1–C28) which had conserved motifs. The subfamily genes were unevenly distributed in 15 chromosomes; chromosome 6 and 7 have the most DoMYB genes. A total of 44 fragment replication events containing 57 DoMYB genes were identified using synteny analysis. In addition, collinear analysis revealed that 70 (54%) pairs of R2R3-MYB genes of Diospyros oleifera were collinear with Arabidopsis thaliana. Upon combining the data from RNA-seq and qRT-PCR, four key genes were screened and identified to correlate with the soluble tannin content during fruit development. DoMYB22 may be related to the synthesis of soluble tannin in persimmon. These results lay an important foundation for further studies on the R2R3-MYB gene function in persimmon fruit development.